Deteksi dini akibat lanjut berat lahir rendah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRAK The probability of acquiring disorders of immunity, psysical, neurologic and mental development is higher in LBW babies. This paper discusses early detection tests for these disorders.